Evaluation of inoculation with asymbiotic nitrogen-fixing microorganisms isolated from rhizosphere of Pinus patula in Colombia - Martínez-Nieto, Patricia; Orozco-Jaramillo, Cielo (BOSQUE, 2009)
The effects on different vegetal parameters of asymbiotic nitrogen-fixing bacteria isolated from the rhizosphere of Pinus patula were studied under greenhouse conditions, in experiments designed for statistical analysis using these forest specie seedlings. This research also examined the interactions of ectomycorrhizal fungus Suillus luteus and the microorganism isolates in P. patula, as well as the nitrogenase activity in these bacteria by acetylene reduction assay. The free nitrogen-fixing bacteria Azotobacter chroococcum, Bacillus macerans, Enterobacter agglomerans and Pseudomonas sp., were isolated of the rhizosphere of P. patula. Their maximum acetylene-reducing values were 120, 18.7, 100, 120 nmol ethylene/tube respectively. Results showed that the best plant growth and nitrogen uptake in the in vivo test in P. patula with these microorganisms and S. luteus were observed with A. chroococcum. According to the longitudinal root cuts in the treatments using S. luteus with A. chroococcum, B. macerans, E. agglomerans, or Pseudomonas sp., the fungus with the agglutinated bacteria was showed around the mycorrhizal root surface only in the S. luteus and B. macerans treatment, but the mycorrhizal infection percentage was low. The inoculation with nitrogen fixing bacteria stimulated longitudinal growth and nitrogenous nutrition of P. patula.